Government Responsibility for Troubled Land Rights Lawsuit - Moh. Imron Fauzi Hidayatullah; Nynda Fatmawati Octarina (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Land registration in Indonesia adheres to a mixed system, a negative system with a positive tendency, meaning that the state does not guarantee the absolute truth of the data presented in the certificate, but as long as no one else filed a lawsuit in court who felt more entitled, so the data in the certificate was proof of strong rights. This research is a non-analytic normative juridical study, the theoretical basis used is the level of normative / contemplative legal theory, the approach in this research is the statute approach. The analysis used is qualitative juridical analysis, namely by collecting and collecting material material, then arranged in a particular framework, then analyzed according to the means of analysis by interpreting the law, legal construction, and legal arguments. From the results of the discussion it was concluded: 1) the lawsuit is judicially premature. The police report cannot be used as a basis for filing a quo lawsuit before obtaining a permanent legal judgment. 2) Lawsuit filed by the Plaintiff less parties (plurium litis consortium), and Lawsuit cannot be accepted (niet ontvankelijk verklaard). 3) The Plaintiff has never owned land that was the Object of the Plaintiff I. The Plaintiff has never owned two land which became Object Plaintiff II but the Plaintiff has signed a power of attorney and a sale and purchase certificate to release ownership of the two land areas. 4) Government Regulation No. 24/1997 introduces the principle of legal certainty as regulated in Article 32 which reflects the shift in the system adopted by land registration in Indonesia from negative system to negative system plus Government.